2021
DOI: 10.3389/fpsyg.2021.626159
|View full text |Cite
|
Sign up to set email alerts
|

Home Learning Environments of Children in Mexico in Relation to Socioeconomic Status

Abstract: We explored the home learning environments of 173 Mexican preschool children (aged 3–6 years) in relation to their numeracy performance. Parents indicated the frequency of their formal home numeracy and literacy activities, and their academic expectations for children’s numeracy and literacy performance. Children completed measures of early numeracy skills. Mexican parent–child dyads from families with either high- or low-socioeconomic status (SES) participated. Low-SES parents (n = 99) reported higher numerac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…However, we did not find relationships between home learning environment indices and children's numeracy skills. This is consistent with other studies that did not observe a relationship between home environment, and numeracy and mathematical skills of Filipino, African American, Chinese, Mexican and Dominican children in low-middle-income communities (Cheung et al, 2018;Leyva et al, 2019;Susperreguy et al, 2021), suggesting that factors other than the home learning environment may also be important targets to foster certain may highlight these additional factors. Alternatively, it is possible that the HLE plays a role, but its contributions are not well captured by the current HLE scales: for example, frequency of activities may be less important than the nature of activities and depth of experiences within thise activities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we did not find relationships between home learning environment indices and children's numeracy skills. This is consistent with other studies that did not observe a relationship between home environment, and numeracy and mathematical skills of Filipino, African American, Chinese, Mexican and Dominican children in low-middle-income communities (Cheung et al, 2018;Leyva et al, 2019;Susperreguy et al, 2021), suggesting that factors other than the home learning environment may also be important targets to foster certain may highlight these additional factors. Alternatively, it is possible that the HLE plays a role, but its contributions are not well captured by the current HLE scales: for example, frequency of activities may be less important than the nature of activities and depth of experiences within thise activities.…”
Section: Discussionsupporting
confidence: 92%
“…A study involving Chilean families showed that parent-supported numeracy activities can have a significant impact in promoting development of early numeracy skills (Susperreguy et al, 2020). However, another study with Mexican families found relationships between home numeracy activities and children's math skills in families from higher SES backgrounds, but not in families from relatively lower SES backgrounds (Susperreguy et al, 2021). Accordingly, researchers in the field have called for more international and interdisciplinary collaboration in order to better capture the nuances of the home math environment (Hornburg et al, 2021).…”
Section: The Home Learning Environment and Early Mathematics Achievementmentioning
confidence: 99%
“…As hypothesized, we found significant variability in caregiver and child mathematical talk during game play. This replicates previous research with lower-income caregivers that shows significant differences in mathematical talk (e.g., [16,17,24]), and underscores the fact that low-income families show a range in home mathematical experiences similar to upper-income families (e.g., [25,[47][48][49][50]). Despite receiving identical instructions and game materials, families had unique approaches to supporting their children's learning.…”
Section: Variability In Mathematical Talk During Gameplaysupporting
confidence: 86%
“…Similarly, there is significant variability in the home mathematics environments provisioned by low-income families [16,24,25]. Low-income caregivers vary in their frequency of engaging children in numeracy activities at home, such as singing number songs, recognizing digits, and learning simple sums [25]. Children from low-income households self-report varied experiences with math-related games at home.…”
Section: Variability Within Low-ses Householdsmentioning
confidence: 99%
“…Several studies indicate that individual child characteristics and later school achievement are associated with families' SES [1,6,7]. For instance, poverty and low parental education seem to be associated with children's poor outcome scores, whereas parents with higher income and education often provide a higher-quality learning environments by having more conversations with their children, being more responsive, and providing more teaching experiences, all of which leads to better child performance [1,8,9].…”
Section: Introduction 1family's Socioeconomic Status and Children's Early Numerical Competenciesmentioning
confidence: 99%